Insights on the effect of macromolecular crowding on transcription and its regulation - Wenxuan Xu; Dylan Collette; Jin Qian; Laura Finzi; David Dunlap (QRB Discovery)
Transcription of DNA into RNA is a fundamental cellular process upon which life depends. It is tightly regulated in several different ways, and among the most important mechanisms are protein-induced topological changes in DNA such as looping. In vivo neither transcription, nor protein-induced looping dynamics exhibited by individual molecules are easily monitored. In vitro single-molecule approaches do offer that possibility, but assays are conducted in rarefied, saline buffer conditions which greatly differ from the crowded intracellular environment. In the following, we describe monitoring both transcription and lac repressor-mediated DNA looping of single DNA molecules in the presence of different concentrations of crowders to bridge the gap between in vitro and in vivo experimentation. We found that crowding shifts the preferred orientation of DNA strands in the looped complex. Crowding also attenuates the rate of transcript elongation and enhances readthrough at the terminator. Clearly, the activities of proteins involved in gene regulation are modified in surprising ways by crowding.